Women-Owned Enterprises in Vietnam : Perceptions and Potential - International Finance Corporation (Washington, DC, 2018)
Small and medium enterprises (SMEs) are vital to Vietnam’s economic growth, accounting for more than 98 percent of all business, 40 percent of Gross domestic product (GDP), and 50 percent of total employment. The number of SMEs grew by around 100,000 in 2016, encouraged in part by increased government efforts to facilitate new business. Vietnam’s women own 95,906 or about 21 percent of formal enterprises. Vietnam has fewer differences between the legal statuses of men and women. However, most banks have yet to consider adopting strategies that cater to women-owned SMEs. Even when women entrepreneurs do qualify for a bank loan, they tend to receive less than what they asked for, and lower amounts than men. This report reframes these and other perceived challenges of serving this segment as an opportunity for banks and other service providers to capture a growing market of savvy businesswomen who seek better services to grow their firms. By recognizing the needs of business women and demonstrating a more nuanced approach to serving them, this report makes the case that championing rather than dismissing women’s preferences can in fact make a big difference in terms of customer acquisition and sales volumes over time.